2008
DOI: 10.1002/ange.200800008
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Activity of Dendritic C60 Monoadducts in Metal‐Free Superoxide Dismutation

Abstract: Water-soluble fullerenes, in particular the tris-malonyl-C 60 derivative 1 (so-called C 3 ), [1] have been shown to exhibit strong antioxidant activity against reactive oxygen species in vitro and to protect cells and tissue from oxidative injury and cell death in vivo.[2] The ability to destroy the toxic superoxide O 2 C À was suggested to be responsible for fullerene antioxidant activity, [3] although its mechanism is still not clear. Dugan and co-workers offered evidence in support of a catalytic superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…[55] This is the main reason for the relatively small energy difference between int1 (in which the electron has not yet been transferred) and int2 (in which superoxide is converted to an oxygen molecule due to the redox process). This is in concordance with the experimental results by Liu and co-workers, [21] who observed that C 3 derivatives with higher reduction potentials presented higher antioxidant activity. Given that a higher reduction potential corresponds to a greater affinity for accepting electrons, this implies more stabilized HOMO and LUMO.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…[55] This is the main reason for the relatively small energy difference between int1 (in which the electron has not yet been transferred) and int2 (in which superoxide is converted to an oxygen molecule due to the redox process). This is in concordance with the experimental results by Liu and co-workers, [21] who observed that C 3 derivatives with higher reduction potentials presented higher antioxidant activity. Given that a higher reduction potential corresponds to a greater affinity for accepting electrons, this implies more stabilized HOMO and LUMO.…”
Section: Resultssupporting
confidence: 94%
“…The relatively high activation barrier found for the reduction/oxidation process (int1!int2 + O 2 ) for the archetypal C 3 compound studied here is consistent with the low antioxidant activity found experimentally, compared to other C 3 -related derivatives with higher reduction potentials. [21] The third intermediate (int3) is substantially more stable than the initial reactants (À137.8 kcal mol…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations